Correlation of Interleukin-6 And Hs-Crp Value in Covid 19 Patients With Severe Symptoms in Makassar Prodia Clinical Laboratory - Mirnawati, Mirnawati; Saroh, Dewi (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2022)
Corona Virus Disease 2019 (COVID-19) is a new infectious disease caused by a novel coronavirus known as Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2).Patients with severe symptoms of Coronavirus disease-19 (Covid-19) experience hyperinflammation and also a cytokine storm which contributes to the high mortality rate. A useful clinical parameter is needed for risk stratification of Covid-19 patients. This study aims to determine the relationship between Interleukin-6 and Hs-CRP values in Covid-19 patients with severe symptoms at the Prodia Makassar Clinical Laboratory. This research is an observational analytic study with a cross sectional approach. The subjects of this study were 30 patients with Covid-19 with severe symptoms, the time of the study was December 2021 - April 2022. Interleukin-6 and Hs-CRP examinations were carried out on the Roche Cobas 6000 automatic device. Analysis of the data using the Pearson-Product Moment Correlation Test using the help of the Statistical Product and Service Solution program. The results of the research analysis showed a significance value of 0.000 < 0.005. The conclusion of this study is that there is a relationship between Interleukin-6 and Hs-CRP in Covid-19 patients with severe symptoms at the Prodia Makassar Clinical Laboratory. The relationship between the two variables is strong and positive so that as HS-CRP increases, IL-6 will also increase.